PENDIDIKAN POLITIK DAN KETERAMPILAN WIRAUSAHA DIGITAL SEBAGAI UPAYA PENINGKATAN KAPASITAS KEPEMIMPINAN GENERASI MUDA DI SMA NEGERI 2 TOBOALI BANGKA SELATAN - Willa Fatika Sari; Novendra Hidayat; Abdul Fatah; Feni Yulianti; Siti Nisaussangadah (Jurnal Abdi Insani, 2026)
Strengthening the capacity of the younger generation is an important strategy in creating superior and competitive human resources. This service activity was carried out at SMA Negeri 2 Toboali with the aim of improving political literacy, building mental-spiritual-based leadership, and fostering digital entrepreneurship skills. The activity method consisted of pre-implementation, interactive implementation, and evaluation through questionnaires and interviews with 65 students. The results of the questionnaire showed that more than 75% of students considered political education and digital entrepreneurship to be very important, 84.4% rated traditional-digital combination marketing as the most effective, and 96.9% emphasized that mental strength is important in building a business. In addition, 81.2% of students stated that they were interested in continuing higher education. The interviews show potential digital business opportunities, such as regional cuisine, online fashion, and digital courses. These findings confirm that the integration of political education, strengthening mental-spiritual character, and digital entrepreneurship is effective in forming a young generation that is characterful, competitive, and economically independent to support sustainable development in Bangka Belitung.